Microeconomics Theory Through Applications - Cooper, Russell; John, Andrew (Open textbook library., 2011)
Russell Cooper and Andrew John have written an economics text aimed directly at students from its very inception. You're thinking, ”Yeah, sure. I've heard that before.“ This textbook, Microeconomics: Theory Through Applications, centers around student needs and expectations through two premises: … Students are motivated to study economics if they see that it relates to their own lives. … Students learn best from an inductive approach, in which they are first confronted with a problem, and then led through the process of solving that problem. Many books claim to present economics in a way that is digestible for students; Russell and Andrew have truly created one from scratch. This textbook will assist you in increasing students' economic literacy both by developing their aptitude for economic thinking and by presenting key insights about economics that every educated individual should know. How? Russell and Andrew have done three things in this text to accomplish that goal: 1. Applications Ahead of Theory: They present all the theory that is standard in Principles books. But by beginning with applications, students get to learn why this theory is needed. The authors take the kind of material that other authors put in ”applications boxes“ and place it at the heart of their book. Each chapter is built around a particular business or policy application, such as minimum wages, the stock exchange, and auctions. Why take this approach? Traditional courses focus too much on abstract theory relative to the interests and capabilities of the average undergraduate. Students are rarely engaged and the formal theory is never integrated into the way students think about economic issues. And traditional books are organized around theoretical constructs that mean nothing to students. The authors' applications-first approach ensures that students will not see chapters with titles like ”Cost Functions“ or ”Short-Run Fluctuations“. They introduce tools and ideas as and when they are needed. Each chapter is designed with two goals. First, the application upon which the chapter is built provides a ”hook“ that gets students' attention. Second, the application is a suitable vehicle a vehicle for teaching the principles of economics. 2. Learning through Repetition: Important tools appear over and over again, allowing students to learn from repetition and to see how one framework can be useful in many different contexts. Each piece of economic theory in this text is first introduced and explained in the context of a specific application. Most are re-used in other chapters, so students see them in action on multiple occasions. As students progress through the book, they accumulate a set of techniques and ideas. These are collected separately in a ”toolkit“ that provides students with an easy reference and also gives them a condensed summary of economic principles for examination preparation. 3. A Student's Table of Contents vs. An Instructor's Table of Contents: There is no further proof that Russell and Andrew have created a book aimed specifically at educating students about economics than their two tables of contents. The Student's Table of Contents speaks to students, piquing their interest to involve them in the economics, and a Instructor's Table of Contents with the economics to better help you organize your teaching—and frankly, you don't need to get excited by economics, you already are.